Entrepreneurial skills for new tourism firm creation in a turbulent context - Dias, Á.; Silva, R.; Patuleia, M.; González-Rodríguez, M.R. (Global challenges and uncertainty in tourism and hospitality: Marketing advancements and value creation, 2025)
The contemporary landscape of tourism destination management is marked by a confluence of challenges, including economic fluctuations, geopolitical uncertainties, and the imperative for sustainable practices.